1994
DOI: 10.1007/bf00599238
|View full text |Cite
|
Sign up to set email alerts
|

Postural effect on cardiac output, oxygen uptake and lactate during cycle exercise of varying intensity

Abstract: Owing to changes in cardiac output, blood volume distribution and the efficacy of the muscle pump, oxygen supply may differ during upright and supine cycle exercise. In the present study we measured, in parallel, circulatory (heart rate, stroke volume, blood pressure) and metabolic parameters (oxygen uptake, lactic acid concentration [la]) during incremental-exercise tests and at constant power levels ranging from mild to severe exercise. In supine position, cardiac output exceeded the upright values by 1.0-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
61
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 16 publications
8
61
1
Order By: Relevance
“…This being the case, then 1) if indeed the reduction of the A 1 of f H in hypoxia is due to lesser vagal withdrawal, then the same should be the case for the reduction of the A 1 of Q ; and 2) the Q st changes during an exercise transient are independent of mechanisms related to vagal withdrawal. Concerning the latter, in supine posture, a condition in which central blood volume is increased (24,29,47), phase I of Q is not evident (25,29), although resting vagal activation is greater supine than upright (25,38). A higher central blood volume would reduce the amount of blood suddenly displaced from the periphery to the heart by muscle pump action, and thus the size of the immediate increase in venous return, thus preventing an efficient Frank-Starling mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This being the case, then 1) if indeed the reduction of the A 1 of f H in hypoxia is due to lesser vagal withdrawal, then the same should be the case for the reduction of the A 1 of Q ; and 2) the Q st changes during an exercise transient are independent of mechanisms related to vagal withdrawal. Concerning the latter, in supine posture, a condition in which central blood volume is increased (24,29,47), phase I of Q is not evident (25,29), although resting vagal activation is greater supine than upright (25,38). A higher central blood volume would reduce the amount of blood suddenly displaced from the periphery to the heart by muscle pump action, and thus the size of the immediate increase in venous return, thus preventing an efficient Frank-Starling mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, SV slightly increases from rest to light exercise intensity and then does not change even if exercise intensity is increased [15]. Since exercise was started from pre-exercise to moderate or heavy exercise in this study, SV should have been constant.…”
Section: Resultsmentioning
confidence: 82%
“…position [2][3][4][5][6][7][8] . In general, the AT and peak VO2, which are determined from cardiopulmonary exercise testing, were lower in the supine position than in the upright position 5)8) .…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported comparisons of cardiopulmonary responses during upright and recumbent (supine) exercises [2][3][4][5][6][7][8] . Generally, it has been reported that work performance in incremental exercise is enhanced in the upright position as .…”
mentioning
confidence: 99%